PENGEMBANGAN SISTEM PENDUKUNG KEPUTUSAN PEMBELIAN INVESTASI LOKASI PEMUKIMAN DI KABUPATEN BULELENG MENGGUNAKAN METODE COMPOSITE PERFORMANCE INDEX BERBASIS WEB - Taufik Ismail; I Made Gede Sunarya; Made Windu Antara Kesiman (Universitas Pendidikan Ganesha, 2013)
This study aims to (1) Designing a Decision Support System Purchasing Investment Locations Settlements in Buleleng regency Method Using Web-Based Composite Performance Index. (2) Implement the Decision Support System Purchasing Investment Locations Settlements in Buleleng regency Method Using Web Based Composite Performance Index. The research method used is a research and development (research and development), aims to develop a Decision Support System (DSS) purchase of residential investment web location. This SPK load data investment criteria settlement locations obtained through interviews using a questionnaire with Mr. I Nyoman Mas Arya Wiryawan (as the housing developer Duta Mas), for the acquisition of data for each criterion obtained from relevant government agencies (the village board in Buleleng regency, part Bappeda spatial and land part PU). Use of this system is easy enough that users of these systems will be given the option to select multiple criteria in accordance with the investment criteria of investors in determining the location of settlements, where each criterion is assigned a weighting of interest (total 100%), with the determination of the scale of investment value. The results of this study form a web Decision Support System which can be used as a means of investment search residential location in Buleleng regency.